PERIOD USE OF LANGUAGE TERMS PANDEMY COVID-19 - Widodo Widodo; Muhajir Syamsu; Uki Masduki (STKIP PGRI Jombang, 2021)
A word or phrase (a combination of words) that is used as a name or symbol and which accurately expresses the meaning of a concept, process, state, or characteristic that is unique in a particular field such as science, technology, art and so on. This study aims to describe the characteristic patterns of various linguistic terms during the Covid-19 pandemic. This study uses a qualitative descriptive approach in which this study does not use numbers but in the form of words to describe the results of the study. The technique used in this study is to use observation and data collection techniques. The results showed that there were 36 data on the pattern of the Covid-19 language terms which were analyzed and then classified into 14 data in the form of English, 8 data in the form of synonyms, 3 data in the form of English abbreviations, 4 data in the form of Indonesian abbreviations and 6 data in acronym form. The implication of this research is that many people use foreign terms such as corona virus, social distancing, physical distancing, and new normal. Therefore, it is necessary for the role of every citizen, government and media during a pandemic to use the Indonesian language in order to protect the sovereignty of the nation.Keywords: language terms, Covid-19